Peran Pemuda Karang Taruna dalam Mengembangkan Wisata Grujukan Tluvalley di Dusun Barong Kulon Desa Candi Kab. Pacitan - Ardiyanto Ardiyanto; Mokhamad Choirul Hudha (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2026)
This study aims to examine the role of youth organizations (Karang Taruna) in the development of the Grujakan Tluvalley tourist attraction in Barong Kulon Hamlet, Candi Village, Pacitan Regency, with a focus on their involvement in the management and development of community-based tourism (CBT). The research employs a qualitative approach with a case study design, where data were collected through semi-structured interviews, participatory observation, and documentation involving youth members, tourism managers, and the local community. The findings indicate that youth play an important role in operational management, digital promotion, and community-based tourism activities, supported by strong values of mutual cooperation and natural resource potential. However, several challenges remain, including limited funding, lack of training opportunities, and inadequate infrastructure. These findings highlight that youth act not only as implementers but also as key drivers and innovators, emphasizing the need for capacity building through continuous training and institutional support. Theoretically, this study enriches the discourse on youth participation in tourism, while practically providing recommendations for village governments and stakeholders.